2014
DOI: 10.1186/1756-3305-7-232
|View full text |Cite
|
Sign up to set email alerts
|

Humoral responses in Rhodnius prolixus: bacterial feeding induces differential patterns of antibacterial activity and enhances mRNA levels of antimicrobial peptides in the midgut

Abstract: BackgroundThe triatomine, Rhodnius prolixus, is a major vector of Trypanosoma cruzi, the causative agent of Chagas disease in Latin America. It has a strictly blood-sucking habit in all life stages, ingesting large amounts of blood from vertebrate hosts from which it can acquire pathogenic microorganisms. In this context, the production of antimicrobial peptides (AMPs) in the midgut of the insect is vital to control possible infection, and to maintain the microbiota already present in the digestive tract.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 67 publications
1
89
1
1
Order By: Relevance
“…; Vieira et al . ). Intriguingly, a recent study on the effect of diet quality showed that the consumption of aged pollen resulted in a marked increase of the abundance of F. perrara compared to other gut bacteria in the hindgut, which was correlated with impaired host development and increased mortality (Maes et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Vieira et al . ). Intriguingly, a recent study on the effect of diet quality showed that the consumption of aged pollen resulted in a marked increase of the abundance of F. perrara compared to other gut bacteria in the hindgut, which was correlated with impaired host development and increased mortality (Maes et al .…”
Section: Discussionmentioning
confidence: 97%
“…Overall, the transcriptional changes induced by F. perrara seem to be reminiscent of a host response towards a pathogen infection rather than a beneficial or commensal gut symbiont (Casteels et al 1993;Evans 2004;Evans et al 2006;Buchon et al 2009;Vieira et al 2014). Intriguingly, a recent study on the effect of diet quality showed that the consumption of aged pollen resulted in a marked increase of the abundance of F. perrara compared to other gut bacteria in the hindgut, which was correlated with impaired host development and increased mortality (Maes et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported in the literature with transformed microorganisms have been conducted using transgenic E. coli cells, which are not part of insect microbial flora and can be easily eliminated by an antibacterial immune response . It is therefore necessary to identify and isolate suitable symbiotic bacteria to reduce treatment rejection.…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Imentioning
confidence: 99%
“…Several studies reported in the literature with transformed microorganisms have been conducted using transgenic E. coli cells, which are not part of insect microbial flora and can be easily eliminated by an antibacterial immune response. 106 It is wileyonlinelibrary.com/journal/ps therefore necessary to identify and isolate suitable symbiotic bacteria to reduce treatment rejection. Recently, two symbiotic microorganisms, Rhodococcus rhodnii LMG5362 and BFo2, were isolated from the hindgut of their hosts Rhodnius prolixus and Frankliniella occidentalis, respectively.…”
Section: Transformed Microorganisms and Virusesmentioning
confidence: 99%
“…Out of the six genes evaluated, the best results in terms of gene silencing and mortality were obtained for JHP , CHI , COE and particularly for AK . The mean larval mortality at the ‘no‐bacteria negative control’ (diet alone – 23.7% mortality) and at ‘bacteria cells with no vector control’ (25.2% mortality) were stable over various experiments, and both presented minimal differences, demonstrating that E. coli HT115(DE3), when ingested by T. absoluta larvae, did not appear to induce an immune response, which is opposite to reports for Bombix mori and Rhodnius prolixus, in which both showed some immune response to the bacteria.…”
Section: Discussionmentioning
confidence: 63%